2021
DOI: 10.1186/s10020-021-00406-z
|View full text |Cite
|
Sign up to set email alerts
|

ADSCs enhance VEGFR3-mediated lymphangiogenesis via METTL3-mediated VEGF-C m6A modification to improve wound healing of diabetic foot ulcers

Abstract: Background Adipose-derived mesenchymal stem cells (ADSCs) are an important focus in regenerative medicine. However, the biological function of ADSCs in the wound repair of diabetic foot ulcers (DFUs) remains unclear. This study aimed to determine the underlying mechanisms of ADSCs involved in the wound healing of DFUs. Methods The cell surface markers cluster of differentiation 34 (CD34), stromal cell antigen 1 (Stro-1), cluster of differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…VEGFC, another form of the VEGF family protein, has a specific homologous region with VEGFA. It can be induced by TNF-α (Li et al, 2018) and improve diabetic foot by improving microvascular regeneration in diabetes ( Zhou, Wei & He, 2021 ). These studies showed that VEGFA, VEGFB, and VEGFC could all be involved in vascular regeneration, including microvascular regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…VEGFC, another form of the VEGF family protein, has a specific homologous region with VEGFA. It can be induced by TNF-α (Li et al, 2018) and improve diabetic foot by improving microvascular regeneration in diabetes ( Zhou, Wei & He, 2021 ). These studies showed that VEGFA, VEGFB, and VEGFC could all be involved in vascular regeneration, including microvascular regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Some growth factors that are related to angiogenesis were evaluated in some studies. As the most important and relevant growth factor in angiogenesis, the level of VEGF is reported to be upregulated in rat ASCs studies (34,37,41,42,45,53,56). It is reported that the level of VEGF, as well as TGF-b, is upregulated in granulations, while it can be further increased by combining the use of bio-modified gel (41).…”
Section: Ascs Promote Neovascularization In Diabetic Wound Modelsmentioning
confidence: 99%
“…This may attribute to the enhancement of endothelial cell secretion function by ASCs. The molecular mechanism of this process is explored by Zhou et al in 2021, indicating endothelial cell is promoted by ASCs to migration and forming tubule via VEGF-C-mediated METTL3/IGF2BP2−m6A pathway in diabetic mice (53). Studies using human ASCs also found a significantly higher level of VEGF in the tissue around the wound, no matter ASCs are harvested from diabetic or healthy individuals (32,39,42).…”
Section: Ascs Promote Neovascularization In Diabetic Wound Modelsmentioning
confidence: 99%
“…Since lymphangiogenesis plays important roles in tissue regeneration and angiogenesis, lymphatic dysfunction can prevent wound healing due to impaired tissue fluid homeostasis [60]. Several studies have indicated that the induction of lymphangiogenesis could be a therapeutic target for impaired wound healing in patients with diabetic ulcers [56,61]. Maruyama et al demonstrated that podoplanin neutralization by anti-podoplanin antibodies inhibited lymphangiogenesis in a model of ear skin wound healing and inhibited tube formation by human lymphatic endothelial cells in vitro [59].…”
Section: Podoplanin In Wound Healingmentioning
confidence: 99%